Paciente con astigmatismo residual ocasionado por una herida penetrante corneal - Arrobo Suriaga, Sergio Joel (2021)
The clinical case deals with a 45-year-old patient who, as a result of a street fight, suffers a penetrating wound, for which he is transferred to a health center for a corneal suture, which lasts for a period of time. 3:00 p.m. to 5:00 p.m. After an interval of 2 months, the anterior chamber is reformed, after this procedure, therapeutic contact lenses are placed. The described scenario caused residual astigmatism due to surgery in the patient; For this reason, the present research aims to analyze the management of ocular trauma that the patient had and the causes that induced residual astigmatism. It is important to mention that residual astigmatism is a refractory error that occurs after a surgical intervention; Therefore, whatever the technique used, generates a direct influence on the visual result of the person who has been operated on, since the impact is proportional to the size of the corneal incision. For which, physical, objective and complementary examinations were carried out; For this reason, the use of a descriptive, observational and retrospective research on the information presented by the patient under study was considered, with the aim of obtaining as much information as possible about the state of the person, who in his last consultation presented vascularization Inferior corneal, free pupillary area, where post-operative optical correction was indicated: + 1.00-3.00x 27 * of the affected eye, obtaining the final version of visual acuity 20/40.